Levels and avidities of antiphosphatidylethanolamine antibodies in patients with thrombotic events and immunologically-mediated diseases - Kuchar, Oliver; Petrackova, Milada; Kalousová, Marta; Nosková, Libuše; Zima, Tomáš; Fialová, Lenka (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2023)
AIMS: Antiphosphatidylethanolamine antibodies (aPE) represent one type of antiphospholipid antibody (aPL) directed against the neutral phospholipids - phosphatidylethanolamines. The aim of this study was to evaluate levels and avidities of aPE in several groups of patients and compare them with conventional aPLs. METHODS: aPE were analysed in a cohort consisting of 68 hospitalized patients. The other cohort comprised 22 patients with immunologically-mediated diseases. The control group consisted of 20 healthy persons. ELISA methods were used for determination of aPL. Avidities of aPE were tested by modified ELISA with urea as a chaotropic agent. RESULTS: aPE IgG/IgM were significantly higher in the group of patients with venous thromboembolism than those with non-thrombotic internal disorders (P=0.02 for both Ig classes). aPE IgG/IgM elevated above cut-off values were found in 10.8% of patients with venous thromboembolism and as a single aPL in 6.5%. Levels of aPE IgG higher than our limit (>6 U/mL) were detected in 29% of patients with immunologically-mediated diseases with other positive aPL. Low-, intermediate- and high-avidity aPE IgG were found in patients of both cohorts. The avidities of aPE IgG differed from those of anticardiolipin antibodies IgG. Neither aPE IgG levels nor avidity dynamics significantly changed during follow-up. CONCLUSION: aPE may be related to venous thromboembolism and may be part of the repertoire of aPL in immunologically-mediated diseases. There are patients with thrombosis negative for conventional aPL but positive for aPE. aPE IgG may have different avidities.
Keywords: Immunoglobulin G; žilní tromboembolie; Animals; Venous Thromboembolism; Thrombosis; imunoglobulin M; Lupus Erythematosus, Systemic; systémový lupus erythematodes; lidé; trombóza; Hominidae; zvířata; imunoglobulin G; Immunoglobulin M; Humans